Changes in Agriculture Land Usage for Development of Housing (Studies in Tambakrejo Village Jombang District) - Andri, Muhammad; Winarsih, Rini; Rafiie, Mohammad (JURNAL AKTA, 2025)
The rise of housing development by developers on active agricultural land means the government must ensure national food security. Although Law No. 41 of 2009 concerning Protection of Sustainable Food Agricultural Land has been enacted, the reality is that in many cities many agricultural lands close to urban areas have been converted into residential areas. This is the background for the author to examine "The Legal Certainty Aspects in Conversion of Agricultural Land for Housing (Study in Banjardowo Village, Jombang District, Jombang Regency)”. This research uses a statue approach combined with a case approach so that it is normative juridical. The process of analyzing this data was carried out descriptively analytically, namely examining the conversion of agricultural land into housing based on Law No. 41 of 2009 concerning Protection of Sustainable Food Agricultural Land (UU PLP2B) and also associated with the regional spatial plan of Jombang district. The legal consequences of changing the use of agricultural land for housing development if it violates the provisions of the UU PLP2B in the sense that the changed agricultural land is classified as LP2B, then even if it already has a licensing document, it is null and void. For this reason, it must be handled seriously by applying the sanctions contained in Article 70 of the UU PLP2B.The Jombang District Government's efforts to overcome the many changes in the use of agricultural land for housing development have preventively conducted socialization related to the UU PLP2B, accompanied by stipulating Jombang District Regional Regulation Number 10 of 2021 concerning the Regional Spatial Plan of Jombang District for 2021-2041. Also through the relevant agencies, namely the Investment and One-Stop Integrated Services Agency (DPMPTSP), the Agriculture Office, the National Land Agency (BPN), the Public Works and Spatial Planning Office (PUPR), and the Regional Development Planning Agency of Jombang Regency, focus, select and organize in carrying out their coordination related to licensing services. Repressively, it is to increase supervision of developers related to license ownership and deal with problems of violations of the PLP2B Law thoroughly in order to foster a deterrent effect for developers or other community members.